Root growth of forest species as affected by acid soil infertility factors - do Vale, Fabiano Ribeiro; Furtini Neto, Antonio Eduardo; Renó, Nilton Braga; Fernandes, Luiz Arnaldo; Resende, Álvaro Vilela (Pesquisa Agropecuaria Brasileira, 1996)
Pregerminated seeds of 15 forest species, as well as cotton and corn seeds were planted in 500 ml pots containing conveniently treated surface soil (oxisol). After roots reached the botton part of the soil, their growth rate in another pot with amended subsoil was used to evaluate acid soil infertility factors, with the following treatments: (i) check; (ii) Ca(OH)2 to raise soil pH to 6.0; (iii) MgO to raise soil pH to 6.0; (iv) CaCl2 to raise Ca to 1.0 cmolc.kg-1 soil. In order to obtain information about expected differences in Al tolerance, the cation exchange capability (C.E.C.) of the root and induced pH changes in nutrient solution were evaluated. Very distinct differences among species in their ability to grow roots on acid subsoil to tolerate Al toxicity and low Ca availability were observed. Such behavior is important to stablish man-made forests with minimum use of amendments. Al tolerance was not correlated with root C.E.C. and with pH induced changes in nutrient solution. Related to pH changes, it is convenient to emphasize that Eucalyptus grandis and Acacia mangium, two of the studied species most tolerant to acid soil infertility factors, showed outstanding capability in decreasing solution pH even when exposed to much more nitrate than to ammonium.